An e-Retailing Supply Chain Subject to Inventory Inaccuracies - Rekik, Yacine; Syntetos, Aris; Jemai, Zied (International journal of production economics, 2015)
One of the implicit assumptions considered in the majority of investigations performed in the area of inventory management is that the physical flow of products in an inventory system is free from defects. The same is hypothesized for the associated information flow. However, various factors may create a difference between the actual physical and information system (IS) flows and perturb their synchronized evolution. The implications of such a discrepancy are particularly prevalent in contemporary supply chains, where sales commitments are based on IS records only. In this paper we model and analyze the impact of inventory inaccuracies on supply chain performance. We first provide an overview of potential errors that may occur within an inventory system and we then propose a general framework to model the impact of inaccuracy errors. Potential errors in both the physical and/or the IS record inventories are considered and optimal analytical solutions are provided for both centralized and decentralized (coordinated and uncoordinated) supply chains for three plausible scenarios: inaccuracy errors are ignored; errors are estimated; the utilization of a Radio Frequency Identification (RFID) technology enables the reduction of the relevant errors. The performance improvements enabled by the availability of error related information and the RFID technology are assessed and managerial insights are provided. The paper concludes with the implications of our work for supply chain design as well as with an agenda for further research in this area.